Corruption and the constant violation of human rights (2019)
The violation of human rights is essential in conflict situations or contexts, given that Staterestructuring, usually linked to internal corruption processes, is constantly linked to theviolation of fundamental rights. Based on this premise, the purpose of this document shouldbe emphasized. It proposes an overview of the way in which corruption establishes asequential structure of human rights violations. Then, it is intended to present an outline ofa historical framework of Colombian corruption, and the different ways in which thisphenomenon has been presented. Likewise, to present the internal armed conflicts of thenation, clearly permeated by state corruption, as a sort of trigger for the current situation inColombia. To finally conclude with immunity from the underlying consequences of theviolation of human rights.